Antigens of Tissue Plasminogen Activator and Plasminogen Activator Inhibitor 1: Correlates in Nonsmoking Japanese and Caucasian Men and Women - Iso, Hiroyasu; Folsom, Aaron R; Koike, Kazuko A; Sato, Shinichi; Wu, Kenneth K; Shimamoto, Takashi; Iida, Minoru; Komachi, Yoshio (Thrombosis and Haemostasis, 1993)
We reported in a 1987 preliminary study that tissue plasminogen activator antigen was significantly higher in American Caucasian men than in Japanese men. To further examine possible differences in fibrinolytic activity between the two races, an expanded study was conducted in a total of 300 nonsmoking men and women aged 47-69 years in two population-based samples: rural Japanese living in Akita and Caucasians living in Minneapolis-St. Paul, MN. Antigens of tissue plasminogen activator (t-PA) and plasminogen activator inhibitor 1 (PAI-1) were measured. Mean t-PA antigen was 2.3 ng/ml higher in Caucasian men than in Japanese men (P <0.001), but no race difference was seen for women (P = 0.59). Mean PAI-1 was higher in Caucasians than in Japanese for both sexes, and the race difference in mean was 1.8 ng/ml for men (P = 0.07) and 4.4 ng/ml for women (P <0.001). Both t-PA and PAI-1 were associated positively with body mass index and blood triglycerides for all sex-race groups, and positively with alcohol intake for Japanese and Caucasian men. Compared to Japanese, Caucasians of both sexes had higher levels of body mass index and blood triglycerides, and lower average intake of alcohol among men. Even when adjusted for body mass index, triglycerides, alcohol and other cardiovascular risk factors, the race difference in mean t-PA antigen persisted for men (P <0.001), as did the difference in mean PAI-1 for men (P = 0.03) and women (P = 0.001). If PAI-1 is a risk factor for coronary heart disease, a higher level in Caucasians than Japanese would correspond to the higher mortality rate from coronary heart disease in the United States than in Japan.